(untitled) - Hill, Kim Quaile (New York, 1993)
This book provides the essential "nuts and bolts" of Texas state and local government. Written by two highly-regarded authorities on Texas politics, The book discusses the many ways that Texas's state and local governments affect citizens' lives.
Keywords: Local government; Texas